Reducing eating disorder symptoms and risk factors using the internet: a meta-analytic review - Melioli, Tiffany; Bauer, Stephanie; Franko, Debra L.; Moessner, Markus; Özer, Fikret; Chabrol, Henri; Rodgers, Rachel F. (The international journal of eating disorders, 2016)
Objective The purpose of this meta-analytic review was, first, to evaluate the efficacy of Internet-based programs in decreasing eating disorder (ED) symptoms, and, second, to identify moderator variables these effects. Method Twenty studies were identified and between-group effect sizes were calculated for ED symptoms and risk factors. Results Compared with control conditions, Internet-based programs successfully decreased body dissatisfaction (d = 0.28, 95% CI [0.15-0.41], p < .001), internalization of the thin ideal (d = 0.36, 95% CI [0.07-0.65], p < .05), shape and weight concern (d = 0.42, 95% CI [0.13-0.71], p < .05), dietary restriction (d = 0.36, 95% CI [0.23-0.49], p < .001), drive for thinness (d = 0.47, 95% CI [0.33-0.60], p < .001), bulimic symptoms (d = 0.31, 95% CI [0.20-0.41], p < .001), purging frequency (d = 0.30, 95% CI [0.02-0.57], p < .05), and negative affect (d = 0.32, 95% CI [0.12-0.52], p < .001). Moderator analyses revealed no impact of data analytic strategy on intervention effects. Similarly, participant risk status was not a moderator for most outcomes. Discussion Internet-based programs are successful in decreasing ED symptoms and risk factors with small to moderate between-group effect sizes.
First published: 26 November 2015
Gesehen am 05.05.2020